ROS are required for the germinative cell proliferation and metacestode larval growth of Echinococcus multilocularis - Tian, Ye; Cheng, Zhe; Ge, Defeng; Xu, Zhijian; Wang, Huijuan; Li, Xiazhen; Tian, Huimin; Liu, Fan; Luo, Damin; Wang, Yanhai (Frontiers in Microbiology, 2024)
The potentially lethal zoonotic diseases alveolar echinococcosis (AE) is caused by the metacestode larval stages of the tapeworm Echinococcus multilocularis.Metacestode growth and proliferation occurs within the inner organs of mammalian hosts, which is associated with complex molecular parasite-host interactions. The host has developed various ways to resist a parasitic infection, and the production of reactive oxygen species (ROS) is one of the most important strategies. Here, we found that scavenging of ROS reduced metacestode larval growth and germinative cell proliferation in in vivo models. Furthermore, using in vitro-cultured metacestode vesicles, we found that increased ROS levels enhanced metacestode growth and germinative cell proliferation, which was achieved by positively activating the ROS-EmERK-EmHIF1α axis. These results indicate that, beside its capacity to damage the parasite, ROS also play critical roles in metacestode growth and germinative cell proliferation. This study suggests that the effects of ROS on parasite 2 may be bidirectional during AE infection, reflecting the parasite's adaptation to the oxidative stress microenvironment.